Understanding Mobile Application Usage Using Battery Status and Wi-Fi Network - Keeyeon Park; Hye-jin Kim (International Telecommunications Society (ITS), 2020)
Since the prevalence of smartphones, the smartphone application (app) industry has penetrated rapidly. Such growth encourages a deeper understanding of mobile user behavior. Using contextual information, previous studies have attempted to understand when users launch different types of app categories. However, most were limited to the number of apps and categories. This study aims to contribute to the general understanding of mobile app usage in a wider range of categories. We analyzed contextual information that influences smartphone users' anxiety, such as the battery state and Wi-Fi network. We empirically examined a distinctive data set that contains mobile log data across a panel of users. As a result, our findings demonstrate that contextual features such as battery charging duration and Wi-Fi connection are highly related to the choice probability of app category usage. It reveals the importance of dynamic conditions incurred from the battery state and Wi-Fi connection when users choose which app to launch. Our findings have practical implications for smartphone app companies who seek app-targeting strategies or marketers who use mobile apps as a means of advertising to interact with potential customers.
Keywords: 330; mobile industry; battery state; choice model; mobile app usage